Mental Health and Substance Use Disparities Among Urban Adolescent Lesbian and Bisexual Girls - Marshal, Michael P. (J Am Psychiatr Nurses Assoc, 2013)
BACKGROUND: Sexual minority girls (SMGs) report large substance use disparities and victimization experiences, yet there is a dearth of research that focuses exclusively on SMGs. OBJECTIVE: To examine substance use and mental health disparities among SMGs and to determine whether disparities were larger for African American compared with European American girls. METHOD: Data were used from Wave 11 of the Pittsburgh Girls Study, a multiple-cohort, prospective study of urban girls. Girls for the current analysis were aged 16 to 19 years. Fifty-five percent were African American. One hundred and seventy-three (8.3%) identified as SMGs, and 1,891 identified as heterosexual. Multiple regression analyses controlling for age, race, and parent education were conducted. RESULTS: SMGs reported a robust pattern of large disparities in externalizing, internalizing, and borderline personality disorder symptoms. There was little evidence to suggest disparities were moderated by race. CONCLUSION: SMGs and their families would benefit from intervention and prevention programs to reduce disparities among this highly vulnerable population.